Improving Social-Emotional Development Through Ball Sharing Games in 5-6 Year Old Children - Yayuk Junarti; Mimpira Haryono; Ela Pebriani (Journal Of Dehasen Educational Review, 2026)
This study aimed to improve the social-emotional development of children aged 5–6 years through the ball-passing game at PAUD Bakti Andesca, Lubuk Sandi District, Seluma Regency. This research was motivated by the relatively low level of children's social-emotional development, particularly in their ability to adapt to situations, follow activity rules, interact with peers, and demonstrate cooperative behavior in group activities. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which was conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects of this study were 15 children aged 5–6 years in Group B. Data were collected through observation and documentation, while data were analyzed using descriptive quantitative analysis with percentage calculations. The results showed that the children's social-emotional development improved from 74% in Cycle I, categorized as Developing as Expected, to 89% in Cycle II, categorized as Very Well Developed, indicating an increase of 15%. Based on the findings, it can be concluded that the ball-passing game is effective in improving the social-emotional development of children aged 5–6 years, particularly in adapting to situations, following activity rules, interacting with peers, and demonstrating cooperative behavior in group activities.